Summa (Quaestiones ordinariae) art. XXV-XXVII - Henry, of Ghent, 1217?-1293 (Ancient and medieval philosophy., 2020)
Dabei leistet es einen Beitrag zur Geschichte der Formen und Pfade der Ideenvermittlung im Mittelalter und zur mittelalterlichen Buchkultur. Die Kollationierung der Handschriften der Artikel XXV-XXVII und die Untersuchung ihrer materiellen Überlieferung haben der Editorin erlaubt, den Prozess der Ausarbeitung, Publikation und Verbreitung einer Portion von Heinrichs Summa über einen längeren Zeitraum in grosser Detailgenauigkeit zu rekonstruieren. Die hier edierten Artikel enthalten ein Kernstück von Heinrichs theologischem und metaphysischem System. In der Behandlung von Einheit, Natur und Leben Gottes entfalten sie eine rationale Darstellung des ersten Prinzips. This book offers the first critical edition of articles XXV-XXVII of the Summa (Quaestiones ordinariae) of Henry of Ghent. At the same time, it contributes to our understanding of the orms and trajectories through which ideas were transmitted throughout the Middle Ages and to medieval book culture. Collating the manuscripts of articles XXV?XXVII and studying their material tradition allowed the editor to reconstruct in great detail how a portion of Henry's Summa was prepared, published and disseminated over a considerable number of years. The primary text presents an authoritative overview of Henry's theological and metaphysical system. In dealing with the unity, nature, and life of God, it unfolds a rational explanation of the first principle.